Topics in the Surgery of the Biliary Tree - Abdeldayem, Hesham (IntechOpen, 2018)
The basic researches and clinical studies on biliary tree diseases continue to advance at a rapid pace. The articles in this book were written by recognized medical experts and researchers from North America, Europe, Asia, and Africa and aim to provide state-of-the-art reviews on the current knowledge and advances in the surgery of the biliary tree. It includes the most recent advances in that field, particularly cholangiocarcinoma, biliary tree injuries, and biliary cysts.